Incidencia de las estrategias metacognitivas de los docentes de matemáticas en el proceso de comprensión, al solucionar problemas de fracción como parte- todo (2018)
Mathematical presents a great variety of problems, from education and from the learning, this investigation shows the educational results of a study realized with that teach mathematics in the urban and rural official sector of Boyacá, Colombia, with respect to how they approach the resolution of fraction problems divides - everything, in contexts continuous, discreet and like reason. The developed investigation was of type qualitative-would operate, since the metacognitive strategies present concrete aspects in the processes of resolution of problems in the educational ones that teach mathematics and that little have been analyzed from the educational task; for the calculation of the sample a probabilistic sampling Two-stage But-Square became (Simple Random sampling for the first and second stage of the sampling), obtaining a sample of 67 professors in carrying out the ofcial sector in the department of Boyacá, as technical of investigation was realized a factory (resolution of problems) of 12 questions, an interview with semi structured questions and the newspaper became of field. A textual analysis through software SPADT was realized (system of textual data analyses), that allowed to know the different topics that the investigation tried. The results show that 33% of the educational ones are linguistic, 10% are semantic and 18% are schematic and 39%, did not give information to this question, with respect to how they work the fraction divides everything concludes that in continuous context 32% were effective, in discreet context 65% guessed right in his answers. In conclusion, it is possible to be affirmed, that educational the urban ones with formation to discipline, concentrate in the use of numerical algorithms (operations), which are bound to exercitations processes, they always want to give the answer quickly, whereas educational rural that they have the basic formation in primary more analytical and is bound to processes of mathematical reasoning.